Faces of Corporate Social Responsibility - Coercion Vs Morality - Jolanta BIEŃKOWSKA; Czesław SIKORSKI (Communications of International Proceedings, 2022)
The corporate social responsibility has become one of the fundamental determinants of organization’s functioning. It has a huge impact on the general morality in the corporate internal and external environment. The genesis and dissemination of this concept have brought many benefits through the observance of the employee rights, respect for the value of work, care for relations with close and distant stakeholders, and drawing attention to the problems of environmental degradation. Consequently, there are many CSR supporters giving applause for every of its manifestations. However, the analysis of motives prompting to take socially responsible actions leads to the conclusion, that the basis is not predominantly an altruistic, philanthropic attitude, but the competitive, legal and cultural compulsion. The aim of the article is to contribute to the discussion on the motives and effects of corporate social responsibility, to articulate the arguments for the conflict between profit maximization and the costs of achieving pro-social goals is a reasonable set of circumstances where reaping benefits from socially responsible activities is the regulating factor.
Keywords: corporate social responsibility; morality; philanthrophy